Transformasi Kesehatan Mental Remaja Melalui Pendidikan Agama Islam di Era Global - Hidayatul Maghfiroh; Ema Sahara; Endang Sri Wahyuni (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to evaluate the role of Islamic religious education in the transformation of adolescent mental health in the global era. This study uses a literature study method by analyzing various related literature sources, including relevant journals, articles and books. The focus of this research includes identifying adolescent mental health problems that are influenced by academic stress, social pressure, social media use, and identity crises. Furthermore, this research explores how Islamic religious education can offer solutions through character development, application of moral values, and implementation of effective educational programs. Data were analyzed by comparing findings from various sources regarding the impact of Islamic religious education on adolescent mental health. The research results show thah Islamic religious education can make a positive contribution to adolescent mental health in a comprehensive way, although there are several limitations in the application and generalization of the results. This research provides insight into the importance of integrating religious principles in efforts to support adolescent mental health in the global era.